Skeletal Muscle Contraction Time and Tone Decrease After 8 Weeks of Plyometric Training - Zubac, Damir; Šimunič, Boštjan (Journal of strength and conditioning research, 2017)
The aim of the study was to examine whether an improvement in jumping performance after 8 weeks of plyometric training (PT) runs in parallel with changes in lower-limb skeletal muscle contractile properties. Using noninvasive tensiomyography (TMG), we assessed contraction time (Tc) and the maximal amplitude of radial displacement (Dm) in 20 subjects (50% men; age 22.4 ± 4.7 years of age), randomly divided in PT group (N = 10; PLYO) and a control group (N = 10; CTRL). The PLYO performed 8 weeks of PT. Tensiomyography was measured in 5 leg skeletal muscles: vastus lateralis (VL), biceps femoris (BF), tibialis anterior (TA), gastrocnemius medialis (GM), and gastrocnemius lateralis (GL). Additionally, we evaluated countermovement jump (CMJ) height improvement on a ground force plate. Assessments were repeated before and after PT. After 8 weeks of PT, CMJ height increased by 12.2% in PLYO (p = 0.015), but not in CRTL. Contraction time, which is related to myosin heavy-chain type 1 (MHC-1) proportion, decreased in VL (-8.7%; p < 0.001), BF (-26.7%; p = 0.032), TA (-32.9%; p = 0.004), and GL (-25.8%; p = 0.044), but not in GM (-8.1%; p = 0.158). The estimated VL MHC-1 proportion decreased by -8.2% (p = 0.041). The maximal amplitude of radial displacement, inversely related to muscle tone, decreased in BF (-26.5%; p = 0.032), GM (-14.9%; p = 0.017), GL (-31.5%; p = 0.017), but not in TA (-16.8%; p = 0.113) and VL (-6.0%; p = 0.654). After PT, jumping performance increased, which was paralleled by decreased Tc and decreased muscle tone. Additionally, adaptations to contractile properties were muscle specific, which is important for future studies. It seems that adjustments were dose dependent, being higher in muscles with lower habitual load.